Some Remarks on a Class of Finite Projective Klingenberg Planes - Akpinar, Atilla; Dogan, Isa; Demirci, Elif; Gurel, Zeynep Sena; Boztemur, Bercem (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this article, we deal with a class of projective Klingenberg planes constructed over a plural algebra of order m. Thanks to this, the incidence matrices for some special cases of the class are obtained. Next, the number of collineations of the certain classes are found. Besides, an example of a collineation for these classes are given. Finally, we achieve to carry the obtained results to more general case.